The role of exochitinase type A1 in the fungistatic activity of the rhizosphere bacterium Paenibacillus sp. M4 - Jankiewicz, Urszula; Swiontek Brzezinska, Maria (Archives of Biological Sciences, 2016)
The aim of the study was to detect the activity and characterize potentially fungistatic chitinases synthesized by rhizosphere bacteria identified as Paenibacillus sp. M4. Maximum chitinolytic activity was achieved on the fifth day of culturing bacteria in a growth medium with 1% colloidal chitin. Analysis of a zymogram uncovered the presence of four activity bands in the crude bacterial extract. The used three-stage protein purification procedure resulted in a single band of chitinase activity on the zymogram. The purified enzyme exhibited maximum activity at pH 6.5 and temperature 45oC, and thermal stability at 40oC for 4 h. In terms of substrate specificity, it is an exochitinase (chitobiose). The amino acid sequence obtained after mass spectrometry showed similarity to chitinase A1 synthesized by Bacillus circulans. The M4 isolate demonstrated the highest growth inhibiting activity against plant pathogens belonging to the genera Fusarium, Rhizoctonia and Alternaria. Fungistatic activity, although to a somewhat lesser degree, was also demonstrated by purified chitinase. The obtained results confirm the participation of the studied exochitinase in antagonism towards pathogenic molds. However, the lower fungistatic effectiveness of the chitinases points to the synergistic action of different metabolites in biocontrol by these bacteria.